TELAAH STATISTIK PARTISIPASI ALUMNI DALAM PEMBENTUKAN KEPENGURUSAN KELUARGA ALUMNI MESIN SANATA DHARMA - Achilleus Hermawan Astyanto; Yulia Venti Yoanita (Jurnal Berdaya Mandiri, 2022)
The alumni gathering for the 25th years Mechanical Engineering of Sanata Dharma triggered the participants to initiate a forum to build communication, synergy and collaboration between alumni and the alma mater as well as informally started the alumni national network. However, four years have passed, the board of management has not been definitively realized. As a result, the initiators still carry out their mandate as ad interim board. This situation is not ideal. As a reflection and evaluation, a regeneration needs to be further conducted to strengthen the collaboration. This paper describes the participation rate of alumni in the formation of the board of management for 2022-2025 period. The result shows that the participation rate increases as the stages ware carried out. In addition, the figure gaining the majority establishes the support.